Case report: Perioperative management of a patient with shapiro syndrome during on-pump cardiac surgery - Boskovic, S.; Ciobanu, V.; Theuerkauf, N.; Bakhtiary, F.; Velten, M. (Frontiers in Cardiovascular Medicine, 2023)
In 1969 Shapiro et al. described a specific triad, consisting of episodic hypothermia, hyperhidrosis, and corpus callosum agenesis (1). Less than 80 cases have been reported till today and the pathophysiological mechanism of this rare disorder remains to be elucidated. Hypothermic episodes differ in duration, frequency, and most important severity between patients. Current expert opinions on the topic involve a dysregulation of the hypothalamic body “thermostat”. The initial drop from base line of 37⁰C (98.6⁰F) to a lower degree results in hyperhidrosis. Commonly, patients experience chills as the body temperature rises during recovery to regular body temperature (2). Other than the typical triad, a wide variety of different symptoms including headaches, hypoglycemia, or changes in blood counts have been reported